Smart Functional Literacy Using ICT to Promote Mother Tongue Language and Inclusive Development among Ethnic Girls and Women in Northern Thailand - Intaratat, Kamolrat; Lomchavakarn, Piyachat; Ong, Eng Tek; Ng, Khar Thoe; Anggoro, Subuh (2023)
This article reports on the results of a participatory action research study that aimed to explore the socio-economic context, Smart Functional literacy, Language Literacy, and ICT literacy of ethnic girls and women in Northern Thailand. Qualitative research methods were used, including documentary studies, interviews, focus group discussions, observations, and participatory training and work-shops. The first finding revealed that within the three main contexts of ethnic girls and women: (1) most of them come from mountainous farming families and receive primary education in their communities; (2) Smart Functional literacy, particularly when embedded with ICT, was well-liked by participants; (3) Mother Tongue language literacy was decreasing in significance compared to Thai, English, and Chinese languages; and (4) ICT literacy was most accessible and beneficial via smartphones and social media. The second finding indicated that Smart Functional literacy could facilitate gender balance and support all key languages. The top three demanded contents were entrepreneurship skills, Thai language, and smart farming. The third finding shows that integrating Smart Functional literacy with Mother Tongue language improved participants' awareness, facilitated their integration with ICT and heritage and crafts, and enabled inclusive development that met all demands of ethnic girls and women, including their Mother Tongue, resulting in increased pride in storytelling and confidence.